PERAN TEKNIK MANAJEMEN STRES DALAM MENINGKATKAN KESELAMATAN IBU DAN PENGALAMAN PERSALINAN POSITIF: SEBUAH STUDI DI LAYANAN KESEHATAN INDONESIA - Ria Julita Sari; Alfi Laili; Iswandi Idris (Jurnal Ilmiah Kebidanan Imelda, 2025)
Maternal safety and childbirth experience are critical aspects of prenatal care, impacting both mother and infant health. This study investigates the effectiveness of stress management techniques on enhancing maternal safety and promoting positive childbirth experiences in a rural Indonesian healthcare setting. Conducted in collaboration with Puskesmas Pangkalan Brandan, Kabupaten Langkat, the study evaluates the use of structured stress management programs aimed at reducing labor-related anxiety, enhancing mental and physical readiness, and ultimately fostering safer childbirth outcomes. Data analysis techniques used in this study include several statistical methods and qualitative analysis. The study was conducted at the Pangkalan Brandan Health Center, Langkat Regency. The sample used in this study were mothers giving birth at the Pangkalan Brandan Health Center, Langkat Regency, totaling 51 respondents. The sample in this study was drawn using a non-probability sampling technique - Accidental sampling. The results indicate a positive correlation between stress management interventions and improved maternal health metrics, highlighting implications for broader maternal healthcare practices. Overall, the results of this study indicate that stress management therapy methods, coupled with adequate social support, can contribute significantly to better childbirth experiences and higher safety for pregnant women at Pangkalan Brandan Health Center.